Determinants of Hypertension in Coastal Communities: A Study in the East Mawasangka Health Center Area, Indonesia - Waode Azfari Azis; Lufiana; Rininta Andriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Introduction: Hypertension is a growing health problem and is one of the leading causes of morbidity and mortality worldwide. Coastal communities in the East Mawasangka Health Center working area show an increasing trend of hypertension cases every year. This study aims to analyze the relationship between family history, obesity, stress, and sodium consumption with the incidence of hypertension. Methods: This study used a cross-sectional design, involving 82 respondents (n=82) from eight villages selected through accidental sampling in the East Mawasangka Health Center, Central Buton Regency, Southeast Sulawesi, from Juni to Juli 2023. Data were obtained through direct interviews using a structured questionnaire. Data were analyzed using the chi-square test to see the relationship between these variables and hypertension. Results: The results of this study showed a p-value for family history (p-value = 0.004 <0.05), obesity (p-value = 0.048 <0.05), stress (p-value = 0.047 <0.05), and sodium consumption (p-value = 0.014 <0.05) with the incidence of hypertension in coastal communities in the East Mawasangka Health Center working area. Conclusion: The study concluded that Family history, obesity, stress, and high sodium consumption are significantly associated with hypertension in coastal residents of East Mawasangka, so intensive and continuous education to the community, practical salt consumption reduction strategies, routine hypertension and obesity screening programs in posyandu, schools, and workplaces need to be strengthened for early detection and appropriate follow-up, accompanied by nutritional and psychological counseling services for individuals with risk factors in coastal communities.